Challenges in Information Retrieval and Language Modeling - Allan, James; Aslam, Jay; Belki, Nicholas; Callan, Jamie; Croft, Bruce; Dumais, Susan; al, Et (SIGIR Forum, 2003)
Information retrieval (IR) research has reached a point where it is appropriate to assess progress and to define a research agenda for the next five to ten years. This report summarizes a discussion of IR research challenges that took place at a recent workshop. The attendees of the workshop considered information retrieval research in a range of areas chosen to give broad coverage of topic areas that engage information retrieval researchers. Those areas are retrieval models, cross-lingual retrieval, Web search, user modeling, filtering, topic detection and tracking, classification, summarization, question answering, metasearch, distributed retrieval, multimedia retrieval, information extraction, as well as testbed requirements for future work. The potential use of language modeling techniques in these areas was also discussed. The workshop identified major challenges within each of those areas. The following are recurring themes that ran throughout: User and context sensitive retrieval Multi-lingual and multi-media issues Better target tasks Improved objective evaluations Substantially more labeled data Greater variety of data sources Improved formal models Contextual retrieval and global information access were identified as particularly important long-term challenges.